2007
DOI: 10.1007/s10551-007-9576-0
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Ethics Instruction, Religiosity, and Intelligence on Cheating Behavior

Abstract: This study examines the influence of ethics instruction, religiosity, and intelligence on cheating behavior. A sample of 230 upper level, undergraduate business students had the opportunity to increase their chances of winning money in an experimental situation by falsely reporting their task performance. In general, the results indicate that students who attended worship services more frequently were less likely to cheat than those who attended worship services less frequently, but that students who had taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 85 publications
6
95
0
5
Order By: Relevance
“…Bloodgood [42] indicates that the higher religiosity student decreases their cheating behavior. La Barbera et al [43] suggested that higher religiosity consumers looked quantity and luxury products purchased did not make them satisfied.…”
Section: Religiosity Moderating Influence Of Satisfaction On Wommentioning
confidence: 99%
“…Bloodgood [42] indicates that the higher religiosity student decreases their cheating behavior. La Barbera et al [43] suggested that higher religiosity consumers looked quantity and luxury products purchased did not make them satisfied.…”
Section: Religiosity Moderating Influence Of Satisfaction On Wommentioning
confidence: 99%
“…Bloodgood, Turnley, and Mudrack (2008) examined the influence of ethics instruction, religiosity, and intelligence as these relate to cheating. Their findings suggested that students who were not highly religious demonstrated less cheating if they had taken a business ethics course.…”
Section: Attendance Of a Course On Ethicsmentioning
confidence: 99%
“…In the literature, researchers have examined various variables (Kish-Gephart et al 2010) related to cheating, such as, demographic variables-age, gender, and grade (Crown and Spiller 1998;Elias 2009;Klein et al 2007;Smith et al 2004), personality variables-Machiavellianism, religiosity (Chen and Tang 2013;Bloodgood et al 2008, 2010, Tang and Tang 2010, self-esteem (Tang and Zuo 1997), moral judgment (Bernardi et al 2004;West et al 2004), love of money Tang 2014;Tang and Chiu 2003;Tang and Liu 2012;Tang and Sutarso 2013), and achievement goals or motivations (Weiss et al 1993). Others have studied social and environmental contexts-classroom climate and personality of teachers (Murdock et al 2001), perceived prevalence of peers' cheating (Andrews et al 2007), or moral support of the family (Park al.…”
Section: Theory and Hypothesesmentioning
confidence: 99%